Socio-economic status of women in micro credit self help groups in Chennai, India / S. Hemavathy Nithyanandhan - Nithyanandhan, S.Hemavathy (2014)

(untitled)
The Microcredit Self Help Group (SHG) programme in India is an important institutional device used to improve the status of women in India in terms of poverty reduction and women empowerment. The SHG is an effective strategy to provide financial services to poor women, who are excluded from accessing financial services, and offered micro credits for their income generating activities and other non-economic loans targeting improvement in the standards of living. The aim of this dissertation was to establish the extent to which women’s participation in SHGs and their involvement in the group activities improved their socio economic conditions. The objective was to study the socio economic status of women in the SHGs in urban areas by comparing the living conditions of the members before joining the programme and their conditions three years after the programme intervention. The programme intervention was expected to reduce the level of poverty and increase the empowerment of women in SHGs. This study confirms the theoretical premise of Micro Credit Paradigms such as Poverty, Financial Sustainability and Empowerment Paradigms and Theory of Joint Lending Liability. This study adds to the empirical evidence in the area of SHGs in an urban setting. Data was collected from the selected women in SHGs formed by government- funded, non-government organisation under the scheme of Mahalir Thittam in the city of Chennai in, Tamil Nadu. A three stage stratified random sampling techniques was adopted. The NGOs were selected as per the demographic region. Both quantitative and qualitative methods were used in the study. The focus of the quantitative study was to investigate whether there were significant differences in income, savings, assets, expenditure, basic amenities, as well as the attitudinal and behavioural changes in the women before and after the intervention of the SHG ii programme. This study used the Gini coefficient and Lorenz curve to find the income inequality and the Structural Equation Modelling (SEM) to study the impact of micro credit in the SHG women. The qualitative part of the study was to gain deeper insights into some of the variables covered under the quantitative study. The quantitative and qualitative analysis helped to study the changes in the social background of the women in SHGs, their economic status and the financial sustainability of the SHGs. The findings showed that the social and economic status of the women members had improved and there was improvement in the level of income, expenditure and savings. The level of self-confidence and self-esteem of the women showed a positive change. The women were more assertive towards community and social matters. The study recommended that the government develop a strong mechanism to monitor the NGOs and SHG leaders (Animators) so that the funds provided by the government would benefit the poor women. Only then these women can be empowered to help themselves, their family and their community.